Editorial - Graham Connelly (Scottish Journal of Residential Child Care)
Welcome to the first issue of SJRCC of the new decade. We publish in the month that has also seen the publication of the reports of the Independent Care Review in Scotland. The review was established in February 2017, following a meeting in October 2016, at which Scotland's First Minister, Nicola Sturgeon, listened to children and young people in care and care experienced adults and made a commitment at the SNP conference. Ms Sturgeon told her party delegates that she intended to commission an independent, 'root and branch review' of Scotland's children in care system.